Experiences Met by The Receiving Teachers in Handling Learners with Hearing Impairments - Enguerra, Marilou (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the experiences of receiving teachers handling learners with hearing impairment in inclusive classrooms at Gubat North Central School, Division of Sorsogon Province, during School Year 2025–2026. Specifically, it determined the teachers’ profile, assessed the level of difficulties encountered in terms of community barriers, social and emotional challenges, academic challenges, classroom environment, and teacher preparedness, examined the relationship between teachers’ profile and these difficulties, and developed the Hear and Teach: Inclusive Teaching Support Guidebook as a proposed intervention. The study was anchored on the Universal Design for Learning Framework, Social Constructivist Theory, Ecological Systems Theory, Teacher Self-Efficacy Theory, and the proposed Inclusive Teaching Competency Interaction Theory. A descriptive–correlational research design was employed involving 20 receiving teachers selected through total enumeration. Data were gathered using a validated researcher-made structured questionnaire, supported by informal interviews, observation, and library research, and analyzed using frequency count, percentage, weighted mean, and Chi-square test of independence. The findings revealed that the respondents were predominantly middle-aged female teachers with extensive teaching experience and relevant inclusive education training who experienced high levels of difficulty across all identified dimensions. Significant relationships were found between selected profile variables and specific categories of difficulties, particularly years of teaching experience and relevant training, while other profile variables showed no significant relationships. The findings underscore the need for sustained professional development, specialized training, adequate instructional and assistive resources, institutional support, and collaboration among schools, families, and community stakeholders. The study recommends the review, validation, and pilot testing of the Hear and Teach: Inclusive Teaching Support Guidebook and Capacity Enhancement Program. The study supports Sustainable Development Goal 4 (Quality Education) and Sustainable Development Goal 10 (Reduced Inequalities) by promoting equitable and inclusive education and strengthening teacher preparedness, institutional support, and collaborative practices for the sustainable implementation of inclusive education.